Coil design for wireless power transfer systems - Wang, Jun Ming (Nanyang Technological University, 2021)
Wireless power transmission (WPT) was discovered in the 1890s by Nikola Tesla and it was based on the principle of mutual inductance to transmit power wirelessly over 2 mutually coupled coils. Ever since, there have been various studies carried out upon the field of WPT as the technology has improved over the time.